Experiences in physical education of other subject teachers. Impact of barriers and opportunities to promote healthy and active lifestyles - Lúcia Gomes; Ramos, M.; Martins, J.; Joana Claro; da Costa, F. C. (AISEP World Congress, 2019)
Background and purpose: Schools and Physical Education (PE) have been recognized as important contexts for the promotion of physically active lifestyles. The achievement of that aim requires sustained cooperation and shared values among all school members. The study analyses teachers’ past experiences in PE and how these experiences are related to the value that they now attribute to PE (Haynes, Miller, & Varea, 2016). Methods: A mix method was used. A questionnaire (Carreiro da Costa & Marques, 2011) about past experience in PE, opinion about PE status and aims, relationship between physical activity (PA) and knowledge of PA guidelines, was applied to 297 teachers (58 male;239 female). From this sample, 24 teachers were selected to be interviewed in the qualitative study. These teachers were divided into three focus groups depending on their early experiences in PE (good experiences, bad experiences or both). The MaxQda was used for the qualitative data analysis. Results: Teachers who have had good experiences in PE, in elementary and secondary school, value the role of PE in the promotion of physical activities and refer the teacher, the curriculum, and a high self-perception of competence as the factors that have contributed to building positive experiences. Conversely, teachers who have had bad experiences do not value the importance of both PE and physical activities in the education of students, and they refer teachers, curriculum, certain equipment, traumatic experiences and a low level of self-competence as explanatory factors of negative attitudes towards PE. Conclusions: These results support the importance of having good early experiences in PE to generate attitudes in teachers that value PE, supporting the significance of PE in promoting active lifestyles. Negative experiences can lead teachers to become barriers that will hinder the promotion of PA in school.